Analisis Faktor Kompetensi Terhadap Kinerja Karyawan Pada Divisi Biskuit Departemen Warehouse PT. Mayora Indah Tbk Jayanti - Gojali Gojali; Putri Angelina; Subhan Subhan (Pusat Riset dan Inovasi Nasional, 2022)
Competition is the one of Competence is one of the factors that influence the performance of employees in the biscuit division Warehouse Department at PT Mayora Indah, Tbk Jayanti. This research is qualitative with descriptive approach. The data collection method used was observation and interviews with five key informants. Data analysis techniques in this study using Miles and Huberman model with steps such as data collection, data reduction, data presentation, and conclusion. The results showed that the competence of employees in Biscuit Division Warehouse Department still needs to be improved, including the recruitment process. Indicators of competence in this research were taken from Spencer, they are knowledge, skills, attitudes, personality, and motives. Some employees have good competence, but some others must continue fostered and directed by trainings, the application of reward and punishment, emotional approach, etc.